PERANAN PERNIKAHAN SATU ETNIS BAGI MASYARAKAT TIONGHOA - Patriantoro, Teguh Hartono (Universitas 17 Agustus 1945 Surabaya, 2019)
The research aims to know (1) the role of marriage with the same ethnic for Chinese peopleand (2) the obstacles for different ethnic relations. The research used qualitative descriptivemethods. The research was conducted in Makassar city. Types and data sources usedprimary and secondary data.. There were 5 (five) informants as samples were interviewedand the results of these interviews were analyzed using several theories. The research resultindicate that (1) the same ethnic marriage for Chinese people have several role forexample, retaining custom, economy consideration of the candidate, culture and custom likediligent and work hard, considerations of business (developing business to be moreadvanced and big), heretics tradition, belief (religion). and past trauma for social friction.(2) Different ethnic relations caused pro and contra. The pro said different ethnic relationsdepend on each person who runs their relationship, agreement and approval from parentsor family also have influence to that relations. Besides, if the candidate comes fromdifferent ethnic it still can be tolerated as long as its person accept to follow the Chinesetradition. Another response also said that it is not a big deal if the candidate not come fromChinese ethnic because the family tree from grandfather and grandmother have mixed withanother ethnic.Keywords: Marriage, Ethnic, Chinese